Acid-Sensing Ion Channel 1a Modulates NMDA Receptor Function Through Targeting NR1/NR2A/NR2B Triheteromeric Receptors. (15th May 2019) - Ma, Chun-Lei; Sun, Hui; Yang, Liu; Wang, Xing-Tao; Gao, Su; Chen, Xiao-Wen; Ma, Zhi-Yuan; Wang, Gui-hua; Shi, Zhen; Zheng, Qing-Yin
Abstract: The over-activation of N-methyl-D-aspartate receptors (NMDARs) is the main cause of neuronal death in brain ischemia. Both the NMDAR and the Acid-sensing ion channel 1a (ASIC1a) are present in the postsynaptic membrane of the central nervous system (CNS) and participate in physiological and pathological processes. However, the specific role played by ASIC1a in these processes remains elusive. We hypothesize that NMDARs are the primary mediators of normal synaptic transmission and excitatory neuronal death, while ASIC1a plays a modulatory role in facilitating NMDAR function. Using various experimental approaches including patch-clamp recordings on hippocampal slices and CHO cells, primary cultures of hippocampal neurons, calcium imaging, Western blot, cDNA transfection studies, and transient middle cerebral artery occlusion (tMCAO) mouse models, we demonstrate that stimulation of ASIC1a facilitates NMDAR function and inhibition of ASIC1a suppresses NMDAR over-activation. One of our key findings is that activation of ASIC1a selectively facilitates the NR1/NR2A/NR2B triheteromeric subtype of NMDAR currents. In accordance, inhibition of ASIC1a profoundly reduced the NMDAR-mediated EPSCs in older mouse brains, which are known to express much higher levels of triheteromeric NMDARs than younger brains. Furthermore, brain infarct sizes were reduced by a greater degree in older mice compared to younger ones when ASIC1a activity was suppressed. These data suggest that ASIC1a activity selectively enhances the function of triheteromeric NMDARs and exacerbates ischemic neuronal death especially in older animal brains. We propose ASIC1a as a novel therapeutic target for preventing and reducing the detrimental effect of brain ischemia in humans. Graphical abstract: Unlabelled Image Highlights: ASIC1a activity enhances NMDAR-mediated currents in both physiological and pathological conditions. The facilitatory effect of ASIC1a on NMDAR activity appears to selectively target NR1/NR2A/NR2B triheteromers. In tMCAO mice, the brain infarct size was larger in more mature animals which expressed more NR1/NR2A/NR2B triheteromers. Disrupting ASIC1a functiondistinctly reduced the infarct size in older tMCAO mouse brains compared to younger ones.